2008
DOI: 10.1017/s0265021508004882
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of the non-invasive cardiac output monitor USCOM-1A in critically ill patients

Abstract: The correlation between the two techniques was acceptable, although relevant systematic and variable errors were detected. USCOM-1A provided adequate data to distinguish non-invasively different shock types in ICU patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Suprasternal Doppler measures blood flow through the aortic valve enabling non-invasive assessment of stroke volume and cardiac output (USCOM, USCOM Ltd., Sydney, Australia). Suprasternal Doppler has been validated against other measures of stroke volume in the emergency department, operating room and intensive care unit and shown to increase in response to PLR, [18, 19]. We therefore used this technique as a non-invasive reference standard for changes in stroke volume with a PLR in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Suprasternal Doppler measures blood flow through the aortic valve enabling non-invasive assessment of stroke volume and cardiac output (USCOM, USCOM Ltd., Sydney, Australia). Suprasternal Doppler has been validated against other measures of stroke volume in the emergency department, operating room and intensive care unit and shown to increase in response to PLR, [18, 19]. We therefore used this technique as a non-invasive reference standard for changes in stroke volume with a PLR in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Followingashortbootingtimethedevicecanbeusedimmediately.Moreover,thetechniqueisreportedtobeeasytouse afterashortteachingperiod [30,31].Validationandreliability studies have been carried out in intensive care studies against invasive hemodynamic monitoring devices such as pulmonary artery catheter and other thermodilution techniqueswithprovenhighcorrelation [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The technique is reported to be easily learned after a short period by non-physicians [29,30]. Previously reported trials investigated the accuracy of USCOM in various settings and most of them found an acceptable agreement between the USCOM CO measurements and those determined by a thermodilution-based method [15,29,22,[31][32][33][34]16,35,20]. Although, it is critical to report, that an inferior accuracy for USCOM was reported by other authors who found that CO measurements by USCOM do not reliably represent absolute values as compared to pulmonary artery catheter thermodilution technique [36,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, arrhythmia, infection and possible pulmonary artery disruption have always been concerns related to the use of a PAC and led to a growing interest in the development of non-invasive hemodynamic monitoring devices [11][12][13]. One less invasive thermodilution-based technique consists of the pulse induced cardiac output device (PiCCO) but exclusively ultrasound-based devices as the USCOM monitor are entirely non-invasive methods for measuring CO [14][15][16][17][18][19][20]. Beside accuracy and the method related risks another crucial criterion consists of the time required for the determination of CO [21].…”
Section: Anesthesiology and Clinical Science Issn 2049-9752mentioning
confidence: 99%